BRAND IMAGE SEBAGAI VARIABEL INTERVENING PENGARUH ELECTRONIC WORD OF MOUTH, SPONSOR-PROGRAM CONGRUENCE, DAN PRODUCT PLACEMENT MEREK KAHI PADA DRAMA KOREA CAFÉ MINAMDANG TERHADAP PURCHASE INTENTION - Nadya Bella Alvisca; Galih Pradananta (Reinforce: Journal of Sharia Management, 2023)
Globalization, particularly in technology, influences the world significantly, exemplified by the Korean Wave phenomenon driving companies to use Product Placement in dramas. This study examines KAHI's Product Placement in the Korean drama Cafe Minamdang and explores the impact of E-WOM, Product Placement, and Sponsor Program Congruence on Purchase Intention, mediated by Brand Image. With non-probability purposive sampling, active FEBI students at UIN SATU Tulungagung who've seen Cafe Minamdang and know KAHI's placement are chosen. Data, analyzed via multiple linear regression, reveals E-WOM doesn't influence Purchase Intention; Sponsor Program Congruence, Product Placement, and Brand Image partially do. An F-test confirms their collective influence. Adjusted R Square at 0.905 indicates 90.5% of Purchase Intention variation stems from e-WOM, sponsor program congruence, and product placement. A Standard Error of Estimate of 0.653799 underscores precision. Path analysis and Sobel test demonstrate Brand Image mediates E-WOM's impact, but not for Sponsor Program Congruence and Product Placement on Purchase Intention.